Effect of the addition of nano glass powder on the compressive strength of high volume fly ash modified concrete - Onaizi, Ali M. (Elsevier Ltd, 2022)
Using high-volume fly ash as a cement alternative has gained popularity among researchers since it reduces CO2 emissions by minimizing cement production. However, the low strength at early ages remains the main barrier to replace cement with significant amounts of fly ash. Due to their abundance and low cost, nanoparticles derived from waste glass bottles may represent a potential material to boost strength at early ages. It possesses sufficient pozzolanic properties to contribute by a pozzolanic reaction which helps to compensate for the early strength loss associated with high volume fly ash (HVFA) concrete. The purpose of this study is to develop HVFA concrete mixture containing glass powder as a nano additive. To accomplish this, two groups of samples were prepared with 50% fly ash as a cement substitute and 5% and 10% waste glass powder as nano additives. Based on the water content, two groups were prepared. Group 1 was prepared with a water/cement (w/c) ratio of 0.5, while group 2 with w/c of 0.45. The results indicated that the workability of concrete was decreased when glass nanoparticles were added for both groups. However, with regard to compressive strength, the study discovered a significant improvement, particularly when 5% glass nanoparticles were used, which demonstrated high performance comparable to that of control samples of normal concrete.